The characterisation and cetane number determination of synthetic diesel fuels - Forrester, Robert David (Department of Chemical Engineering, 2016)
South African synthetic fuel plants produce large quantities of lower alkenes which can be catalytically oligomerized to liquid transportation fuels. In the screening of experimental catalysts for the production of diesel-range fuels, it is important to measure the quality, as well as the quantity, of the fuel being produced. Cetane number is an important indicator of the quality of a diesel fuel ru1d is measured by a standard engine test (ASTM D 613) which requires l litre of fuel and is therefore not suitable for the routine testing of the small volumes of fuel produced by experimental catalysts. Alternative cetane number prediction methods exist but these have generally been developed to predict the cetane number of crude-oil based fuels and are therefore not suitable for use with synthetically derived fuels. This thesis details the development of a formula which accurately predicts the cetane number of a fuel from other, easily measured parameters. Several samples of fuel were produced under varying reaction conditions and were hydrogenated to ensure that they were virtually 100% alkane. Differences in cetane number should therefore be due to differences in the degree of branching. By measuring the cetane number on a. standard test engine and correlating the result with the amount of branching as measured by ¹Hnmr, a formula was developed which was found to accurately predict the cetane number of these types of synthetic fuels. The results obtained also show that for the conversion of ethene over a supported nickel catalyst, cetane number decreases as temperature increases. This decrease is probably caused by secondary butane oligomerization reactions.